Fungal Species Associated with Date Palm (Phoenix dactylifera L.) Fruit and Tiger Nut (Cyperus esculentus L.) Fruit in Lafia Metropolis, Nasarawa State, Nigeria - , Olukayode Olugbenga Orole; , Ignesta O. Okolo; , Victor Fadayomi; , Dauda I. Odonye; , Amos Ohiobo (Archives of Current Research International, 2017)
Aims: Fungi are ubiquitous microorganisms that bring about large scale spoilage of plants and animal products. The resultant effects include contamination of products and disease conditions in colonized living host. The aim of the study is to enumerate and identify fungal species associated with date palm and tiger nut fruits in Lafia, Nasarawa State. Methodology: Date fruit and Tigernut fruits samples (60 each) were collected from the six markets located in the Lafia metropolis. These were evaluated using the pour plate technique to determine fungal load in the samples. Results: Results showed that Date palm obtained fungal population of 0.28x104±7.1 log10 CFU/g as the lowest in Koro Market and Tigernut fruits recorded 4.30x104±3.0 log10 CFU/g as the highest. Seven fungal genera were isolated in Date palm fruits, while 9 were obtained from Tigernut with genera Aspergillus, Penicillium, Rhizopus, Mucor found common to the two fruits. Aspergillus species obtained the highest percentage occurrence of 42.10% in Date fruits, while Chrysosporium xerophilum obtained 3.40% as the lowest in the fruits sampled Conclusion: Findings from the study showed that Tigernuts and Date fruits sold in Lafia market presented heavy burden of fungal contaminations and these contaminants have the capacity of releasing harmful metabolites into the fruits thus making them unsafe for consumption.